Hubungan Sektor Pariwisata terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Gowa - Rahman, Abd.; Rahim, Abd.; Hastuti, Diah Retno Dwi; Irwandi, Irwandi; Astuty, Sri (Jurnal EMT KITA, 2026)
This research aims to analyze the relationship between the tourism sector and Regional Original Income (PAD) in Gowa Regency. The tourism sector is considered to have great potential in increasing PAD through developing tourist attractions and increasing the number of tourist visits. The research method used is a quantitative approach with the Spearman Rank correlation analysis technique. The data used is time series data from 2015 to 2024 which includes the number of tourist attractions, the number of domestic tourists, foreign tourists and Gowa Regency PAD. The research results show that there is a strong and significant relationship between the number of tourist attractions and PAD. Meanwhile, a number of domestic tourists have a positive relationship with PAD. The number of foreign tourists shows a negative relationship. These results indicate that the development of tourist attractions has the most significant influence in increasing Gowa Regency's PAD compared to the number of tourist visits, especially foreign tourists.